Problems and Difficulties in the Additive Manufacturing of Composites with Carbon Fiber Reinforcement for Medical Application - Amit Bhumarker Singh; Abhishek Singh (International Journal of Fracture Mechanics and Damage Science, 2024)
Amputation is more prevalent than one may think due to an accident, war, or disease. Prosthetics and associated orthotics have a combined global market value of $2.8 billion. Carbon fibre has found a market due to increased demand for foot prostheses. Fused deposition modeling (FDM) is a rapidly advancing three-dimensional (3D) printing technique. PEEK (polyether-ether-ketone) is a biocompatible, high-performance polymer that could potentially be utilised as an orthopedic surgery implant material. The mechanical properties and biocompatibility of FDM-printed PEEK and its composites are presently not well-defined; therefore, the development of FDM-printed CFR-PEEK composites with suitable mechanical attributes holds promise for their utilization as biocompatible materials in bone grafting and tissue engineering applications. The goal of this study is to recommend the best implant, which must be robust yet relatively flexible, with a modulus of elasticity as near to that of bone as is feasible. To meet this goal, new polymeric and composite materials must be created.
Keywords: Biocompatible Material; Carbon fiber; Fused Deposition Modeling; PEEK; modulus of elasticity